Improved hydrogen storage properties of Mg/MgH2 thanks to the addition of nickel hydride complex precursors. (5th November 2019) - Galey, Basile; Auroux, Aline; Sabo-Etienne, Sylviane; Dhaher, Sameh; Grellier, Mary; Postole, Georgeta
Abstract: In order to improve the hydrogenation/dehydrogenation properties of the Mg/MgH2 system, the nickel hydride complex NiHCl(P(C6 H11 )3 )2 has been added in different amounts to MgH2 by planetary ball milling. The hydrogen storage properties of the formed composites were studied by different thermal analyses methods (temperature programmed desorption, calorimetric and pressure-composition-temperature analyses). The optimal amount of the nickel complex precursor was found to be of 20 wt%. It allows to homogeneously disperse 1.8 wt% of nickel active species at the surface of the Mg/MgH2 particles. After the decomposition of the complex during MgH2 dehydrogenation, the formed composite is stable upon cycling at low temperature. It can release hydrogen at 200 °C and absorb 6.3 wt% of H2 at 100 °C in less than 1 h. The significantly enhanced H2 storage properties are due to the impact of the highly dispersed nickel on both the kinetics and thermodynamics of the Mg/MgH2 system. The hydrogenation and dehydrogenation enthalpies were found to be of −65 and 63 kJ/mol H2 respectively (±75 kJ/mol H2 for pure Mg/MgH2 ) and the calculated apparent activation energies of the hydrogen uptake and release processes are of 22 and 127 kJ/mol H2 respectively (88 and 176 kJ/mol H2 for pure Mg/MgH2 ). The change in the thermodynamics observed in the formed composite is likely to be due to the formation of a Mg0.992 Ni0.008 phase during dehydrogenation/hydrogenation cycling. The impact of another hydride nickel precursor in which chloride has been replaced by a borohydride ligand, namely NiH(BH4 )(P(C6 H11 )3 )2, is also reported. Graphical abstract: Image 1 Highlights: Mg/MgH2 storage system with improved properties. Hydride complexes used as nickel precursor catalysts for MgH2 doping. Impact on the hydrogenation and dehydrogenation kinetics and thermodynamics. Onset temperature of hydrogen desorption below 200 °C. Absorption of 6 wt% of H2 in less than 30 min at 100 °C.